Preanesthetic Evaluation and Assessment of Children with Down's Syndrome - Letterio B. Santamaria; Carmelo Di Paola; Federica Mafrica; Vincenzo Fodale (The Scientific World Journal)
During preoperative evaluation for anesthesia in the Down patient, it is important to focus attention on the functional conditions of the patient and systems that frequently show anomalies. One of the challenges of evaluating pre-operative conditions and potential risks in the Down patient is the lack of a gold-standard evaluation score; cervical spine abnormalities, reduced dimensions and malformations of the airways, neurological changes, respiratory and cardiac disease, as well as endocrinological and metabolic alterations. We suggest, as a possible method of evaluation for patients with mental retardation and possible malformations, a new scale which takes the functional and mental conditions into account: the Sensorial, Psychological, Anatomical, Biological, Operational and Surgical (SPABOS) Compliance Score.